Sentinel node mapping in the prostate cancer - Sadeghi, R; Tabasi, K.T; Bazaz, S. M. M; Kakhki, V. R. D; Massoom, A. F; Gholami, H; Zakavi, S. R (Nuklearmedizin - NuclearMedicine, 2011)
Aim: Sentinel node (SN) biopsy is becoming a standard procedure in the management of several malignancies. Several groups have evaluated the feasibility and value of this procedure in prostate cancer patients. In the current meta-analysis, we comprehensively and quantitatively summarized the results of these studies. Methods: Several databases including Medline, SCOPUS, Google Scholar, Ovid, Springer, and Science direct were systematically searched for the relevant studies regarding SL biopsy in the prostate cancer (“prostate” AND “sentinel” as search keywords). The outcomes of interest were sensitivity and detection rate of the procedure. Results: For detection rate and sensitivity 21 and 16 studies met the criteria of inclusion respectively. Pooled detection rate was 93.8% (95% CI 89–96.6%). Cochrane Q value was 216.077 (I2 = 89.81% and p < 0.001). Pooled sensitivity was 94% (95% CI 91–96%). Cochrane Q value was 14.12 (I2 = 0.0 and p = 0.516). Conclusion: SL biopsy can prevent unnecessary pelvic lymph node dissection in prostate cancer patients. This procedure is feasible with low false negative rate and high detection rate.
Keywords: Prostate cancer; sentinel node biopsy; lympho scintigraphy; meta-analysis